Analysis of Accuracy Nursing Care Process Implementation - Tejo Trisno; Nursalam Nursalam; Mira Triharini (Jurnal Ners, 2020)
Introduction: Implementation of the nursing care process is still a problem in nursing services. The problem found in the nursing process is the accuracy of nurses in applying the nursing care process. The aim of this study to analyze the accuracy of the implementation of the nursing care process.Methods: This study was as a descriptive analytics design with 100 respondents. Samples were selected using cluster sampling. Data were collected using a questionnaire that has been tested for validity and reliability. The variables included assessment, nursing diagnosis, nursing plan, nursing implementation, evaluation, and nursing documentation. Data were analyzed in a descriptive form consisting of good, sufficient and fewer categories. The standard for implementing the accuracy of the nursing process is 100%.Results: The result showed the accuracy of implementation nursing care, namely 64% assessments are sufficient, 69% of nursing diagnosis is sufficient, 59% of nursing plans are sufficient, 66% of nursing implementation is sufficient (), along with 60% of nursing care evaluation and 62% of nursing care documentation.Conclusion: The accuracy of the nursing care process describes the quality and patient safety and is useful for patients, nurses, and the health team. Further studies must be conducted to analyze  factors related to accuracy of the implementation of the nursing care process.